The friends we keep [compact disc, unabridged] - Green, Jane, 1968- (Penguin Audio, 2019)
Maggie, Evvie, and Topher met one another during their first week at university and instantly bonded, keeping in touch through all of life's troubles. When they finally reunite 30 years later, however, a lurking secret untold threatens to ruin their happiness.